Role of cancer-associated fibroblasts in the progression, therapeutic resistance and targeted therapy of oesophageal squamous cell carcinoma - Xue, Mengying; Tong, Yusuo; Xiong, Yaozu; Yu, Changhua (Frontiers in Oncology, 2023)
Oesophageal squamous cell carcinoma (ESCC) is one of the most aggressive malignant tumours with high morbidity and mortality. Although surgery, radiotherapy and chemotherapy are common treatment options available for oesophageal cancer, the 5-year survival rate remains low after treatment. On the one hand, many oesophageal cancers are are discovered at an advanced stage and, on the other hand, treatment resistance is a major obstacle to treating locally advanced ESCC.Cancer-associated fibroblasts (CAFs), the main type of stromal cell in the tumour microenvironment, enhance tumour progression and treatment resistance and have emerged as a major focus of study on targeted therapy of oesophageal cancer.With the aim of providing potential, prospective targets for improving therapeutic efficacy, this review summarises the origin and activation of CAFs and their specific role in regulating tumour progression and treatment resistance in ESCC. We also emphasize the clinical potential and emerging trends of ESCC CAFs-targeted treatments.